**SOLUTION:**

__Using statement (1)__

m^{3 +} 380 = 381m

=>m^{3 }-380m –m +380 = 0 or

=>m^{3} –m – 380m +380 = 0

=>m(m² - 1) - 380(m - 1) = 0

m(m+1)(m-1) - 380(m-1) = 0

(m-1) [ m(m+1) - 380 ] = 0

(m-1)(m² + m - 380) = 0

(m-1)(m+20)(m-19) = 0.

__This implies m=1, m= -20, m=19. Hence we do not have one specific value for m.__

**(INSUFFICIENT)**

** **

__Using statement (2) __

We can have m that can be any negative integer.

**(INSUFFICIENT)**

** **

__Using both (1) and (2) __

From m=1, m= -20, m=19, at m= -20

We have 2(- 20) + (-20)^{3 }< 0, satisfying statement (2)

__At m = 1 and m= 19 we won’t have statement (2) satisfied__.

__Thus m= -20 by combining both .( SUFFICIENT)__

**Thus ****OPTION(C)**